Perolehan Sertifikat Hak Milik Atas Tanah Berdasarkan Putusan Pengadilan - Satriana, I Made Wahyu Chandra; Dewi, Ni Made Liana; Sunarbowo, Dewa Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
This study aims are to examines in depth the validity of certificates made based on court decisions on land ownership rights confirmation when compared to certificates made through other processes and the legal force of land ownership certificates made based on court decisions. This study uses an empirical research method. The data sources for this study are library research by taking theories and opinions of scholars through their work related to the problem and field research, namely data obtained by conducting field research both in government agencies and the community. The results of this study are that court decisions that have permanent legal force can be used as the basis for applying for land ownership certificates, as a substitute for deeds made before the Land Deed Making Officer (PPAT) as proof of the transfer of ownership rights to a plot of land, as long as the truth of the court decision cannot be proven, it is better for the party who feels disadvantaged.